Feasibility of Reinforced Concrete Monolothic Beam Column Joints in Different Seismic Zones - Wala, Aqeel Ali Shams Wagla (AMC Indian Journal of Civil Engineering, 2021)
The present paper emphasizes the design of R.C. monolithic beam-column joints for strength criteria and to find out feasibility of the structure designed for Zone 2 and Zone 5 as per IS1893(Part1):2002, incorporating ductility provisions of IS13920:1993. For this research a moment resisting RCC frame is modeled and analyzed for above mentioned seismic zones. After analyzing, resultant frames are then designed as per IS 456. An Internal Beam Column Joint form first, third, and top floor is selected and designed manually for nominal shear strength so as to compare it with shear developed in the same joints provided by the software. The software of choice for this paper is ETABS.